Analisis Ketersediaan Pasokan Listrik di PT PLN (Persero) UPK Teluk Sirih dengan Metoda Lean Six Sigma - Muhammad Dani Gitatisna; Agus Sutanto (METAL: Jurnal Sistem Mekanik dan Termal, 2021)
This research was conducted to analyze electricity supply availability from the steam power plant at PLN Teluk Sirih. This electricity supply availability is also called the equivalent availability factor (EAF). The regular efforts made to maintain the EAF at PLN are still corrective, by repairing the damage that has occurred, and no systematic method has been implemented. Accurate analysis is required to achieve high EAF values and precision so that the problem's root cause can be resolved. This can be done by using the lean six sigma method. This method can identify waste and solve problems quickly. The methodology used is Define, Measure, Analyze, Improve, and Control (DMAIC). The waste that occurs is a defect, which is the inability of the power plant to supply electricity to customers (PLN P3BS). The identification results show that the factors that influence EAF are boiler tube leak (41.46%), DS Phase S (20.45%), equipment vibration (5.85%), bottom ash system (5.39%), and other disorders (26.84%). The EAF calculation for the last two years is 70.93%, and the six sigma level is 2.05. The improvement design is expected to eliminate boiler tube leak and increases the EAF by 6.65%. Thus, the EAF value becomes 77.85%, and the six sigma level becomes 2.26.